The Acquisition of Conjoined-Clause of An Indonesian Child - Rosihin Rosihin (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
The objectives of this study were to analyze the language acquisition for conjoined-clauses in speaking of an Indonesian child who got exposures from English cartoon films and opportunities to practice with his linguistic environment. This research was qualitative research and it was longitudinal study where the data were collected for twelve months ( April 2016 – March 2017) by recording his spontaneous speech when the subject was 4.10 until 5,9 years old. The data were transcribed then analyzed to see the development of his English syntactic constructions of conjoined-clause. The finding of the research showed that the process of language acquisition of the subject closely followed the universal principles of language acquisition for conjoined – clauses. By giving exposure of English cartoon film everyday for three hours and opportunities to practice with his linguistic environments, the acquisition of foreign language learner can be similar to first or second language learner.